ANALISIS HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA WAROENG JMK (JEMBATAN MERAH KLATAKAN) DI SITUBONDO - Antika, Sindy; Sari, Lita Permata; Minullah, Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Marketing is an activity carried out by companies to market or promote goods or services. The purpose of this study was to analyze and test the effect of price, service quality, and purchasing decisions on consumer satisfaction at Waroeng JMK (Jembatan Merah Klatakan). The sampling technique in this study used a simple random sampling technique. Data analysis and hypothesis testing in this study used the Partial Least Square-Structural Equation Model (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application showed that price had a significant positive effect on purchasing decisions, service quality had a significant positive effect on purchasing decisions, price had a positive effect but not significant on consumer satisfaction, service quality had a significant positive effect on consumer satisfaction, purchasing decisions had a positive effect but not significant on consumer satisfaction. The results of the indirect effect hypothesis test showed that the price variable had a positive effect but not significant on consumer satisfaction through purchasing decisions , service quality had a positive effect but not significant on consumer satisfaction through purchasing decisions.